Sun house eaudiobook A novel. - Duncan, David James (2023)
An epic comedy about love, spirit, and the quest for transcendence in an anything-but-transcendent America, from the author of the perennial cult bestsellers The River Why and The Brothers K . A random bolt from a DC-8 falls from the sky, killing a child and throwing the faith of a young Jesuit Jesuit into crisis. A boy's mother dies on his fifth birthday, sparking a lifetime of repressed anger that he unleashes once a year in reckless duels with the Fate, God, or Power who let the coincidence happen. A young woman on a run in Seattle experiences a shooting star moment that pierces her with a love that will eventually help heal the Jesuit, the angry young man, and innumerable others. The journeys of this unintentional menagerie carry them to the healing lands of Montana and a newly founded community—where nothing tastes better than Maker's Mark mixed with glacier ice, and nothing seems less likely than the soul-filling delight a troupe of spiritual refugees, urban sophisticates, road-weary musicians, and local cowboys begin to find in each other's company. With Sun House , David James Duncan continues exploring the American search for meaning and love that he began in his acclaimed novels The River Why and The Brothers K . This stunning novel, set amid the gorgeous landscapes of the American West, illuminates the contemporary world through the prisms of Eastern wisdom, cast-off ecstatic religious ideals, and the unpredictable, expansive yearnings of the human heart.